The Challenges of Shariah Penal Code and Legal Pluralism in Aceh - Muhammad Razi; Khairil Azmin Mokhtar (Jurnal Media Hukum, 2020)
An outstanding feature of Aceh Special Region is its autonomy relating to the administration of Islamic Criminal justice system. Undoubtedly this power is one of the key features of the devolution of power to the region. It is a tedious process with numerous challenges and obstacles. The research paper aims to examine whether the prolonged development pertaining to the Islamic Criminal justice system's administration is due to the constitutional and administrative arrangements or actually lies in society. Devolution requires well-structured and systematic planning and execution. It involves various mechanisms and touches many issues. To blame the system for protracted progress is not something unexpected. However, the perception of the public or society of Aceh relating to the Shariah Criminal Justice System also has a significant impact. The research shows that despite the general manifestation of the local population's willingness and support for the system, some issues have emerged. The research reveals that the challenges and obstacles in prolonged development come from both the society and the system. Lack of understanding of the society towards Syariah Penal Code, problems faced by members of the People Representative Council (DPR) Aceh in drafting the Code, and the need to ensure strict compliance of the Code with Syariah are among obstacles faced. The issues and their effect on the implementation and enforcement of Aceh's Syariah Penal Code are scrutinized in the research paper.  This is a qualitative study based on library and internet research. It is also legal research whereby the relevant laws are examined.  The devolution in Aceh is more complicated than in other regions because it is coupled with "dualisme hukum" or legal pluralism within the Indonesian legal system.